2014
DOI: 10.1186/scrt443
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Umbilical cord tissue-derived mesenchymal stem cells induce apoptosis in PC-3 prostate cancer cells through activation of JNK and downregulation of PI3K/AKT signaling

Abstract: IntroductionAlthough mesenchymal stem cells (MSCs) have antitumor potential in hepatocellular carcinoma and breast cancer cells, the antitumor mechanism of human umbilical cord mesenchymal stem cells (hUCMSCs) in prostate cancer cells still remains unclear. Thus, in the present study, we elucidated the antitumor activity of hUCMSCs in PC-3 prostate cancer cells in vitro and in vivo.MethodshUCMSCs were isolated from Wharton jelly of umbilical cord and characterized via induction of differentiations, osteogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
(46 reference statements)
2
42
1
Order By: Relevance
“…Previous studies that investigated a possible role of WJMSC in oncology have shown that these cells not only reduce the growth rate in human breast carcinoma [8] and prostate cancer [9], but also inhibit the proliferation of human osteosarcoma, ovarian carcinoma, Burkitt's lymphoma [10] and glioblastoma multiforme [31] cell lines in vitro. These findings are in keeping with the inhibiting effect exerted specifically by WJMSC on SCC-LCSC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that investigated a possible role of WJMSC in oncology have shown that these cells not only reduce the growth rate in human breast carcinoma [8] and prostate cancer [9], but also inhibit the proliferation of human osteosarcoma, ovarian carcinoma, Burkitt's lymphoma [10] and glioblastoma multiforme [31] cell lines in vitro. These findings are in keeping with the inhibiting effect exerted specifically by WJMSC on SCC-LCSC.…”
Section: Discussionmentioning
confidence: 99%
“…from amniotic fluid, umbilical cord blood and umbilical cord) harbor therapeutic potential in cancer treatment, as they can target the tumor site and reduce tumor burden [7]. In particular, WJMSC have been reported to reduce the growth of human breast carcinoma [8], prostate cancer [9], osteosarcoma and ovarian carcinoma cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…WJ-MSCs possess cytokines and growth factor receptors, which allow them to be vital tools for cancer therapy. In such therapy, WJ-MCSs drastically weaken the cancerous tumors by secreting therapeutic proteins which promote the cancerous cells to undergo cell death and to stop the cell cycle [46]; moreover, WJ-MSCs enhance the immune response to cancer cells. With the minimum risk of spreading the cancer cells throughout the body or to the MSC donor, WJ-MSCs have the potential to serve as vehicles for delivery of tumor suppressive genes and anticancer drugs occur.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that AT-MSCs increase cell viability of prostate tumor cell lines LNCaP and LNCaP-Bic, but no effect was observed for Du145 or PC3. UC-MSCs induce apoptosis in prostate cancer cell line PC-3 and attenuate bladder tumor cell growth in vitro and in vivo 36. However, BM-MSCs do not inhibit the proliferation of renal cell carcinoma cell lines (RCC42 and RCC52), but increase their migratory ability and invasiveness in vitro 37.…”
Section: Mscs In Anticancer Therapiesmentioning
confidence: 99%